Carbon neutral policy in action: the case of Bhutan. (3rd July 2019) - Yangka, Dorji; Rauland, Vanessa; Newman, Peter
ABSTRACT: Climate policy across the world is proceeding at a highly variable pace, with some places very committed to decarbonizing their economies and others just beginning. Emerging nations are generally just starting along this journey. However, among the few nation states that have pledged to achieve carbon neutrality, is Bhutan, a least developed country. Carbon neutrality is an ambitious climate policy that is increasingly being recognized as necessary in order to stabilize global temperature rise at 1.5°C. However, Bhutan is likely to face significant challenges in maintaining this status as the country balances its desire to grow in economic opportunities (GDP) and in human happiness (GNH). Little research has been conducted inside the policy processes to better understand how Bhutan will maintain carbon neutrality. Through open-ended, semi-structured interviews with key stakeholders, this study provides an inside view on the current situation and future challenges that Bhutan may face, along with the complexities associated with implementing and maintaining an ambitious carbon neutral policy. The paper highlights Bhutan's story and how it could be useful for policy learning and knowledge sharing, especially in the context of emerging nations' climate governance.